Menstrual Hygiene Practices and Awareness among Adolescent Girls in Government Schools of Karachi, West - Hussain , Ghazal (Nurture, 2014)
This study was done to evaluate the menstrual hygiene practices of the low-income adolescent girls living in Karachi Pakistan. Data was collected from one hundred and twenty nine adolescent girls aged 9-14 from three government schools of Karachi, West. Altogether 29 questions were asked from each of them. It was found out that the menstrual hygienic practices were un-satisfactory. The girls need to be educated about the use of proper pads, its changing and proper disposal. This can be achieved by giving them proper education, training and knowledge by family members and teachers so there won’t be any misunderstanding to the adolescent girls regarding menstrual hygiene.